The Aesthetics and Politics of Linguistic Borders Multilingualism in Northern European Literature - Grönstrand, Heidi; Huss, Markus; Kauranen, Ralf (Taylor & Francis, 2020)
This collection showcases a multivalent approach to the study of literary multilingualism, embodied in contemporary Nordic literature. While previous approaches to literary multilingualism have tended to take a textual or authorship focus, this book advocates for a theoretical perspective which reflects the multiplicity of languages in use in contemporary literature emerging from increased globalization and transnational interaction. Drawing on a multimodal range of examples from contemporary Nordic literature, these eighteen chapters illustrate the ways in which multilingualism is dynamic rather than fixed, resulting from the interactions between authors, texts, and readers as well as between literary and socio-political institutions. The book highlights the processes by which borders are formed within the production, circulation, and reception of literature and in turn, the impact of these borders on issues around cultural, linguistic, and national belonging. Introducing an innovative approach to the study of multilingualism in literature, this collection will be of particular interest to students and researchers in literary studies, cultural studies, and multilingualism.